DCEP as a bridge to ongoing therapies for advanced relapsed and/or refractory multiple myeloma. Issue 12 (2nd December 2018) - Yuen, Hiu Lam Agnes; Low, Michael Sze Yuan; Fedele, Pasquale; Kalff, Anna; Walker, Patricia; Bergin, Krystal; Coutsouvelis, John; Grigoriadis, George; Spencer, Andrew
Abstract: There is limited data describing dexamethasone, cyclophosphamide, etoposide, and cisplatin (DCEP) in relapsed refractory multiple myeloma (RRMM). We reviewed 65 patients with RRMM receiving DCEP between 2005 and 2017 in two Melbourne Hospitals. Patients had received a mean of three prior treatment lines (range, 1–11). The mean number of cycles of DCEP was two (range, 1–4). Overall response rate (ORR) was 55% whilst 19% achieved MR and SD. Median overall survival (OS) was 9.6 months. Those bridged to autologous stem cell transplant (ASCT) had significantly improved OS compared to those who were not (median 32.8 vs. 10.7 months, p =.0004). Significant treatment-related mortality (TRM) was observed (9.7%), mostly attributable to grade 3–4 neutropenia and febrile neutropenia. Mandatory use of G-CSF is, therefore, warranted to prevent septic complications. In heavily pretreated RRMM, DCEP is an effective bridge to definitive therapy but in the absence of the latter, its value is questionable.